CULTURAL BOUND BEHAVIORS AND ATTITUDES IN ENGLISH CLASS (Al'Adalah, 2004)
Language and culture constitute a unity. Language cannot be taught completely separated from the habits and culture of the native speakers. For a teacher teaching a foreign language which is not his own would often encounter lots of problems. Different cultures between languages including different forms and uses of gestures invite many common obstacles in communication Teachers should assume a neutral attitude when teaching a language. To teach a foreign language he should watch a lot behaviours and attitudes of the native speakers while they are communicating verbally